Faktor Internal dan Eksternal yang Memengaruhi Underpricing pada Saat IPO di Bursa Efek Indonesia - Kemas Nurcholish Thoriq; Sri Hartoyo; Hendro Sasongko (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2018)
This study aims to examine the variables that influenced the underpricing stock price when the company put its initial public offering in Indonesia Stock Exchange of the 2010-2015 period. The dependent variable in this study was underpricing measured by the value of initial returns, while the independent variables included ROA, DER, company age, company size, type of Industry, underwriter’s reputation, exchange rate and inflation. The data used in this study were secondary data collected by using purposive sampling method. The samples of 135 companies from were taken from 137 population companies conducted IPOs from 2010-2015 in Indonesia Stock Exchange. This study used logistic regression for data analysis. The results of this study showed that ROA, DER, age and inflation influenced the level of underpricing is proven. Other variables influencing the level of underpricing is not proven. This research model showed that the independent variables explained the variation in the level of underpricing of 89.6%.Keywords: underpricing, internal and external factors, ROA, DER